DEVELOPMENT OF A COMPUTATIONAL MODEL FOR C02 MANAGEMENT BY INTEGRATING DIFFERENT BUILDING SYSTEMS IN MALAYSIA - ELHASSAN AHMED, SAMI MUSTAFA MOHAMED (2015)
Environmental management of construction projects is very complicated due to existence of many constraints, such as cost and time. This research presents a theoretical basis of Business oriented Environmental Management System (B-EMS) for construction projects in Malaysia. It consists of developing the appropriate conceptual framework and computational model for managing C02 emissions of construction phase.